2020
DOI: 10.1080/00438243.2021.1891963
|View full text |Cite
|
Sign up to set email alerts
|

European agricultural terraces and lynchets: from archaeological theory to heritage management

Abstract: Terraces are highly productive, culturally distinctive socioecological systems. Although they form part of time/place-specific debates, terraces per se have been neglected-fields on slopes or landscape elements. We argue that this is due to mapping and dating problems, and lack of artefacts/ecofacts. However, new techniques can overcome some of these constraints, allowing us to reengage with theoretical debates around agricultural intensification. Starting from neo-Broserupian propositions, we can engage with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 95 publications
(128 reference statements)
0
24
0
1
Order By: Relevance
“…There are two ways to differentiate agricultural terraces: horizontal layout (planform) and vertical profile. The horizontal layout can strictly follow the contour lines, can form braided structures or lynchets 75 , or, alternatively, they can compose wave-like terraces 49 or off-contour terraces 76 . Moreover, Brown et al 75 identified regular box-like terrace structures and, together with Wei et al 49 , referenced pocket/half-moon shaped terraces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two ways to differentiate agricultural terraces: horizontal layout (planform) and vertical profile. The horizontal layout can strictly follow the contour lines, can form braided structures or lynchets 75 , or, alternatively, they can compose wave-like terraces 49 or off-contour terraces 76 . Moreover, Brown et al 75 identified regular box-like terrace structures and, together with Wei et al 49 , referenced pocket/half-moon shaped terraces.…”
Section: Introductionmentioning
confidence: 99%
“…The horizontal layout can strictly follow the contour lines, can form braided structures or lynchets 75 , or, alternatively, they can compose wave-like terraces 49 or off-contour terraces 76 . Moreover, Brown et al 75 identified regular box-like terrace structures and, together with Wei et al 49 , referenced pocket/half-moon shaped terraces. Pocket terraces also have a wall-free “spontaneous” version 76 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cucchiaro et al (2020) demonstrate that orthomosaics from drones provided an accurate and high level of detail of the terrace landscape, the archaeological features and sediment stratigraphy along an excavation trench previously unobserved. Similarly, Brown et al (2021) show the beneficial use of drones to map multi-faceted terraces under intensification and diversification. In landscape archaeology, Stek (2016) demonstrates the utility of drones for detecting previously undocumented subsurface archaeological artifacts in mountainous, Mediterranean landscapes.…”
Section: Drones As Social Science Research Toolsmentioning
confidence: 97%
“…For example, Cucchiaro, Fallu [51] demonstrate that orthomosaics from drones provide an accurate and high level of detail of the terrace landscape, the archaeological features and sediment stratigraphy along an excavation trench previously unobserved. Similarly, Brown, Walsh [52] show the beneficial use of drones to map multi-faceted terraces under intensification and diversification. In landscape archaeology, Stek [53] demonstrates the utility of drones for detecting previously undocumented subsurface archaeological artifacts in mountainous, Mediterranean landscapes.…”
Section: Drones As Social Science Research Toolsmentioning
confidence: 98%